Does Ethical Investment Perform Differently? A Comparative Study on SRI Index Performance in North America - Xiao, Qian (2013)
Socially responsible investment has increased rapidly in growth in the last few years and it has attracted great attention on their financial performance. This study investigates the comparative performance of SRI index relative to the conventional index in both Canadian and U.S. market. The entire sample period has been divided into two sub-periods - Pre-crisis and Post crisis - in order to examine the influence of the recent financial crisis on the performance of the indices. In addition to the traditional finance measures of Sharpe, Treynor and Jensen measures, the econometric methods of OLS regression with dummy variables and GARCH (1, 1) models are also applied as the performance measurements. The main finding of this study indicated that the incorporation of social screening process does not affect the financial performance. Specifically, the results imply the SRI indices do not perform differently from respective conventional indices. In addition, the SRI indices tend to have a positive implication. Therefore, investors will not be financially sacrificed for investing in an ethical index. Whilst the recent financial crisis had a great influence on the volatility, it had no significant effect on the average return of all studied indices. It can be noted that there is a difference between the Canadian and U.S. capital market in terms index performance.